CLINICAL AND ANATOMICAL BASIS OF OPENING AND DRAINAGE OF PHLEGMONS OF THE EYE AREA - Gadayev Asliddin Mamarasulovich; Eshmurodov Shodiyor Qobil o'g'li (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Annotation: This article explores the clinical and anatomical underpinnings of opening and drainage procedures for phlegmons in the eye area. By examining the literature, we aim to provide insights into the methods employed, the results achieved, and the implications for clinical practice. This comprehensive analysis contributes to a better understanding of the surgical management of periorbital infections.